2016
DOI: 10.1016/j.jbi.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Extractive text summarization system to aid data extraction from full text in systematic review development

Abstract: Objectives Extracting data from publication reports is a standard process in systematic review (SR) development. However, the data extraction process still relies too much on manual effort which is slow, costly, and subject to human error. In this study, we developed a text summarization system aimed at enhancing productivity and reducing errors in the traditional data extraction process. Methods We developed a computer system that used machine learning and natural language processing approaches to automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Duplicate data extraction should be considered in the absence of other approaches to minimize extraction errors. However, much like systematic reviews, this area will likely see rapid new advances with machine learning and natural language processing technologies to support researchers with screening and data extraction [47,48]. However, experience plays an important role in the quality of extracted data and inexperienced extractors should be paired with experienced extractors [46,49].…”
Section: Some Frequently Asked Questions About Methodological Studiesmentioning
confidence: 99%
“…Duplicate data extraction should be considered in the absence of other approaches to minimize extraction errors. However, much like systematic reviews, this area will likely see rapid new advances with machine learning and natural language processing technologies to support researchers with screening and data extraction [47,48]. However, experience plays an important role in the quality of extracted data and inexperienced extractors should be paired with experienced extractors [46,49].…”
Section: Some Frequently Asked Questions About Methodological Studiesmentioning
confidence: 99%
“…A potential problem that clinical user face is the management of the results set to identify, appraise, and synthesize the best available evidence to answer the clinical question in the best possible manner. In all this process, a lot of manual effort is required to extract the data to make a summary, and it is also subjected to error [27]. Moreover, the context of the user may change the default ranking of an article to bring it to the top or take it to the bottom.…”
Section: Methodsmentioning
confidence: 99%
“…At this point, the system is restricted to biomedical research papers only, but the authors intend to extend it to other types of SRs. A similar approach is followed by Bui et al (2016) The present document has been produced and adopted by the bodies identified above as author. This task has been carried out exclusively by the author in the context of a contract between the European Food Safety Authority and the author, awarded following a tender procedure.…”
Section: Classification Methodsmentioning
confidence: 99%
“…A more general information extraction algorithm was discussed by Basu et al (2016) who employ natural language processing (NLP) and machine learning to build information extraction algorithms to identify data elements in new publications without having to go through manual annotation to build golden standards for each data type. A similar approach was provided by Bui et al (2016). More information on these methods is provided in Section 2.2.2.…”
Section: Critical Appraisal and Synthesis Stage Of A Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation